Salivary proteomics and metaproteomics identifies distinct molecular and taxonomic signatures of type-2 diabetes - Diana Samodova; Evelina Stankevic; Mathilde Sonne Søndergaard; Naiyu Hu; Tarunveer S. Ahluwalia; Daniel R. Witte; Daniel Belstrøm; Anniek Frederike Lubberding; Pratik D. Jagtap; Torben Hansen; Atul S. Deshmukh (Microbiome)
Abstract Background Saliva is a protein-rich body fluid for noninvasive discovery of biomolecules, containing both human and microbial components, associated with various chronic diseases. Type-2 diabetes (T2D) imposes a significant health and socio-economic burden. Prior research on T2D salivary microbiome utilized methods such as metagenomics, metatranscriptomics, 16S rRNA sequencing, and low-throughput proteomics. Results We conducted ultrafast, in-depth MS-based proteomic and metaproteomic profiling of saliva from 15 newly diagnosed T2D individuals and 15 age-/BMI-matched healthy controls (HC). Using state-of-the-art proteomics, over 4500 human and bacterial proteins were identified in a single 21-min run. Bioinformatic analysis revealed host signatures of altered immune-, lipid-, and glucose-metabolism regulatory systems, increased oxidative stress, and possible precancerous changes in T2D saliva. Abundance of peptides for bacterial genera such as Neisseria and Corynebacterium were altered showing biomarker potential, offering insights into disease pathophysiology and microbial applications for T2D management. Conclusions This study presents a comprehensive mapping of salivary proteins and microbial communities, serving as a foundational resource for enhancing understanding of T2D pathophysiology. The identified biomarkers hold promise for advancing diagnostics and therapeutic approaches in T2D and its associated long-term complication Video Abstract